Textiles of southeast Asia trade, tradition and transformation - Maxwell, Robyn ([Hong Kong] Periplus Editions, 2003)
Textiles provide a visual history of a country's culture and crafting traditions in a way few other things can accomplish. In Textiles of Southeast Asia, Dr. Robyn Maxwell provides the definitive work on Southeast Asian textiles.Traditional textiles are one of the most widely collected and important categories of Southeast Asian art. Using an extensive range of locally produced raw materials and an astonishing array of techniques--including applique, weaving, batik and embroidery--the textiles of Southeast Asia are astonishing in their versatility and originality. Textiles are used to fashion everything from everyday clothing to sacred and ceremonial costumes, shrouds and wrapping cloths, hangings, banners and ritual regalia--all of which are represented and explained in Textiles of Southeast Asia.This authoritative text focuses on the changing relationship between indigenous Southeast Asian traditions and the outside influences continuing to be brought to the area, which change the nature of the region's textile traditions. This book considers the various ways Southeast Asian textile artisans reacted over the centuries to the steady stream of new and powerful ideas and raw materials arriving from India, China, the Islamic world and Europe. A detailed and definitive resource, Textiles of Southeast Asia is a welcome addition to the field of textiles.
Available also in print format (FA-4346)
Keywords: Textile fabrics -- Southeast Asia -- Themes, motives